To Be or Not To Be T4: Evidence of a Complex Evolutionary Pathway of Head Structure and Assembly in Giant Salmonella Virus SPN3US - Ali, Bazla; Desmond, Maxim I.; Mallory, Sara A.; Benítez, Andrea D.; Buckley, Larry J.; Weintraub, Susan T.; Osier, Michael V.; Black, Lindsay W.; Thomas, Julie A. (Frontiers in Microbiology, 2017)
Giant Salmonella phage SPN3US has a 240-kb dsDNA genome and a large complex virion composed of many proteins for which the functions of most are undefined. We recently determined that SPN3US shares a core set of genes with related giant phages and sequenced and characterized 18 amber mutants to facilitate its use as a genetic model system. Notably, SPN3US and related giant phages contain a bolus of ejection proteins within their heads, including a multi-subunit virion RNA polymerase (vRNAP), that enter the host cell with the DNA during infection. In this study, we characterized the SPN3US virion using mass spectrometry to gain insight into its head composition and the features that its head shares with those of related giant phages and with T4 phage. SPN3US has only homologs to the T4 proteins critical for prohead shell formation, the portal and major capsid proteins, as well as to the major enzymes essential for head maturation, the prohead protease and large terminase subunit. Eight of 50 SPN3US head proteins were found to undergo proteolytic processing at a cleavage motif by the prohead protease gp245. Gp245 undergoes auto-cleavage of its C-terminus, suggesting this is a conserved activation and/or maturation feature of related phage proteases. Analyses of essential head gene mutants showed that the five subunits of the vRNAP must be assembled for any subunit to be incorporated into the prohead, although the assembled vRNAP must then undergo subsequent major conformational rearrangements in the DNA packed capsid to allow ejection through the 30 Å diameter tail tube for transcription from the injected DNA. In addition, ejection protein candidate gp243 was found to play a critical role in head assembly. Our analyses of the vRNAP and gp243 mutants highlighted an unexpected dichotomy in giant phage head maturation: while all analyzed giant phages have a homologous protease that processes major capsid and portal proteins, processing of ejection proteins is not always a stable/defining feature. Our identification in SPN3US, and related phages, of a diverged paralog to the prohead protease further hints toward a complicated evolutionary pathway for giant phage head structure and assembly.